Al-Muhassinat Al-Badi'iyah in the Book of Love in the Qur'an by Muhammad Saeed Ramadan Al-Bouti - Muis, Muhsin; Faruq, Umarul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2023)
: Rhetoric is the highest level of linguistic sciences. The lowest level of speech is that which begins with words that indicate their specific meanings, then it gradually reaches the eloquent word and the eloquent phrase. This research reveals the ingenious benefactors and their types contained in the book